2011
DOI: 10.2310/jim.0b013e318220df41
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Genetic Variants in Vitamin D Metabolism and Asthma Characteristics in Young African Americans: A Pilot Study

Abstract: Introduction Low vitamin D levels have been associated with asthma severity in children. Young, urban African Americans (AA) have high rates of hypovitaminosis D and asthma. Our objective was to determine associations between variants in vitamin D metabolism genes and asthma characteristics in a pilot study of young urban AAs. Materials and Methods Two urban AA cohorts of subjects aged 6 to 20 years (139 subjects with asthma and 74 subjects without asthma) were genotyped for 12 single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…The known influence of VDR on the immune response [6,7,8] may have contributed to or even accounted for the impact of the VDR rs2228570 polymorphism on allergy. Previous observations revealed an influence of the FokI VDR polymorphism on prevalance and/or clinical course of asthma [27,28], immune type 1 diabetes [77], multiple sclerosis [31], systemic lupus erythematosus [78], graft rejection [79], ulcerative colitis [40], aggressive periodontitis [30] and dengue hemorrhagic fever [80]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The known influence of VDR on the immune response [6,7,8] may have contributed to or even accounted for the impact of the VDR rs2228570 polymorphism on allergy. Previous observations revealed an influence of the FokI VDR polymorphism on prevalance and/or clinical course of asthma [27,28], immune type 1 diabetes [77], multiple sclerosis [31], systemic lupus erythematosus [78], graft rejection [79], ulcerative colitis [40], aggressive periodontitis [30] and dengue hemorrhagic fever [80]. …”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of VDR have been reported to be associated with bone mineral density [23] diabetes mellitus [24,25], hypertension [26], asthma [27,28], periodontitis [29,30], risk of multiple sclerosis [31,32] and malignancy [33,34,35,36,37,38]. On the other hand, several studies failed to report an impact of VDR polymorphisms on multiple sclerosis [39], inflammatory bowel disease [40], coronary artery disease [41] or malignancy [42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a recent study [213] on a group of 305 patients with histopathologically confirmed melanoma found no correlation between SNPs in CYP27B1 (rs4646536), CYP24A1 (rs927650), vitamin D binding protein VDBP (rs1155563, rs7041) and melanoma risk [213]. Other studies indicated an association of CYP24A1 SNP (rs2248137) with lower vitamin D levels, and the CYP2R1 SNP (rs10766197) was linked to asthma [215]. Another study confirmed association between three SNPs in CYP27B1 and multiple sclerosis [216].…”
Section: Vitamin D3 Activation and Inactivation In The Skinmentioning
confidence: 99%
“…Examination of single nucleotide polymorphisms (SNPs) in genes involved with vitamin D metabolism and signaling, particularly CYP24A1 (the main enzyme to degrade 1,25(OH) 2 D 3 ), have shown that there is a heritable component of the vitamin D status in families with asthma [15,16]. Vitamin D deficiency is believed to contribute to asthma pathogenesis by promoting steroid resistance, AHR and airway remodeling [17,18].…”
Section: Vitamin D and Asthmamentioning
confidence: 99%